Uses of the Biographical Approach : The Construction of Youth Technobiographies - Lemus, Magdalena (Forum.)
In this article, we report on our analysis as part of a research project conducted from 2012 to 2018, and we explore the potential of the biographical approach in studying the appropriation of digital technologies (DTs). The biographical approach (SAUTU, 2012) is described as a theoretical-methodological strategy to address how people, through time and space and within the framework of certain cultural and socioeconomic contexts, connect with various digital technologies and how they construct meanings, practices, and relationships. With the analysis of a series of technobiographies (CHING & VIGDOR, 2005) of young people, we reflect on the ability of the method to capture the symbolic dimension of access to DTs, reconstruct the acquisition of digital skills and their role in educational transitions, and understand the links between biographical trajectories and broader social processes, such as those that constitute and reproduce social inequalities in contemporary societies. We show that technobiographies are a useful construct to identify repetitions, trends, and patterns of behavior, but also to pinpoint anything that is out of the ordinary in the paths of the appropriation of DTs of each particular group.